Assessment of Facial Golden Proportions in Chinese Adults in Hunan Province - Shrestha, Neesha; Khanal, Abhilasha; Wei, Xiao Li (Orthodontic Journal of Nepal, 2018)
Introduction: The interest of facial esthetics is growing in orthodontics. Golden proportion has been intriguing in the field of esthetics. There is a need of evaluation of facial golden proportions in various population groups. Objective: To evaluate the relationship between facial parameters and golden proportion among patients for better treatment planning. Materials & Method: Cross-sectional study design was used. Out of 356 pre-treatment frontal photographs, skeletal and dental Class I (n=186) were differentiated on the basis of 0.7°≤ANB≤4.7° and molar relationship. Then samples were stratified according to research criteria (Class I=159). After standardization of photographs, printing was done. The landmarks were plotted on photographic prints and parameters were measured manually. Analysis was done using SPSS version 20.0. Result: Most of the facial height proportions TR-ME:LC-ME (1.66±.08), LC-ME:TR-LC (1.54±.09), TR-LN:LN-ME(1.58±.16),LC-CH:CH ME(1.57±.16) in frontal photographs of Class I were more close to the golden proportion. However, facial width proportions showed deviation from the golden proportion. Conclusion: The vertical proportions in the patients showed closer to the golden proportion compared to the width proportions, indicating more soft tissue balance in vertical height.